2013
DOI: 10.5901/ajis.2013.v2n2p497
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Politics of Local Government Budgeting in Nigeria (1995-2011)

Abstract: The poor performances of most local government councils in Nigeria had squarely centered around the politics of local government budgeting in the country. A cursory look at the project profile of all the local government councils in Nigeria (1995Nigeria ( -2011 1995-2011, revealed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, Ocheni, Atakpa andNwankwo (2013) reported that poor performance of local governments in Nigeria squally centered on the politics of budgeting at the local government level. The failure and unethical nature of local governments budgeting has been a major concern to policy makers, political analyst, researchers, and citizens at for most local governments in developing countries.…”
mentioning
confidence: 99%
“…However, Ocheni, Atakpa andNwankwo (2013) reported that poor performance of local governments in Nigeria squally centered on the politics of budgeting at the local government level. The failure and unethical nature of local governments budgeting has been a major concern to policy makers, political analyst, researchers, and citizens at for most local governments in developing countries.…”
mentioning
confidence: 99%
“…Meanwhile tax is a compulsory levy imposed by Government on individuals and companies for the various legitimate function of the State (Olaoye, 2008). According to Ocheni et al, (2013) the statutory allocation from the federation account, serving as the main source of revenue to local government, is said to be inadequate and untimely received by the local government administration to enable discharge their obligations. Adenugba and Chike (2013) define revenue sources as the funds required by the government to finance its activities.…”
Section: Introductionmentioning
confidence: 99%